Purification and expression of a novel bacteriocin, JUQZ-1, against Pseudomonas syringae pv. Actinidiae (PSA), secreted by Brevibacillus laterosporus Wq-1, isolated from the rhizosphere soil of healthy kiwifruit - Shuai, Yang; Langbo, Yi; Yi, Yang; Danni, Chen; Qingzhong, Peng (Frontiers in Microbiology, 2025)
Kiwifruit canker, caused by Pseudomonas syringae pv. actinidiae (PSA), has led to significant losses in the kiwifruit industry each year. Due to the drug resistance feature of PSA, biological control is currently the most promising method. Developing biocontrol bacteria against PSA could help solve the issue of drug resistance generated during the chemical control of PSA to a certain extent. In this research, a Wq-1 strain that demonstrated excellent inhibitory activity against PSA was isolated from the rhizosphere soil of healthy kiwifruit. Based on the morphological characteristics and phylogenetic analysis of the 16S rRNA gene sequence, the isolated strain was identified as Brevibacillus laterosporus Wq-1. Bacteriostatic proteins were isolated from the cell-free culture filtrate of strain Wq-1 and were found to have a molecular weight of approximately 12 kDa, as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). Liquid chromatography–tandem mass spectrometry (LC–MS/MS) detection revealed that there were several peptides in the target band that were consistent with protein 01021 in the genome. The gene of the 01021 protein was cloned into the plasmid pPICZa, and the recombinant bacteriocin was successfully expressed using the Pichia pastoris X33 expression system. The recombinant protein 01021 effectively inhibited the growth of PSA. This is the first report of the protein’s antimicrobial activity, distinguishing it from previously identified bacteriocins. Therefore, we named this bacteriocin JUQZ-1. In addition, our results showed that the protein JUQZ-1 not only exhibited a broad bacteriostatic spectrum but also high thermal and pH stability suitable for harsh environmental conditions., JUQZ-1, a protein with antimicrobial properties and strong environmental tolerance, may serve as a promising alternative to antibiotics.